Financial Cycles and Bankruptcies in the Nordic Countries - Jan Hansen (Sveriges Riksbank, 2003)
This paper studies the relationship between macroeconomic imbalances and bankruptcies in the Nordic countries. Finland, Sweden, Norway and Denmark liberalised their financial markets during the 1980s and experienced the consecutive emergence of a financial cycle, followed by severe banking crises. Cointegration analysis and Granger causality tests suggest that the joint path of credit, house prices and possibly investment in construction relative to GDP creates macroeconomic imbalances and has high predictive power for bankruptcies. House prices appear to be most important. Several empirical results appear to be similar for Sweden, Finland and Norway, while patterns for Denmark often differ. The estimations indicate that macroeconomic imbalances were small at the end of 2001 in all four countries.
Keywords: C22; E32; E44; 330; Macroeconomic imbalances; financial distress; VAR model; cointegration